Pulmonary Valve Anatomy and Abnormalities: A Pictorial Essay of Radiography, Computed Tomography (CT), and Magnetic Resonance Imaging (MRI). Issue 1 (January 2016) - Jonas, Samuel N.; Kligerman, Seth J.; Burke, Allen P.; Frazier, Aletta Ann; White, Charles S.
Abstract : Given its inconspicuous appearance on radiography, computed tomography (CT), and magnetic resonance imaging (MRI) the pulmonary valve (PV) is often overlooked as an important cause of both cardiac and pulmonary disease. In this pictorial essay, we review the normal appearance of the PV as well as various congenital anomalies including pulmonary atresia, pulmonary stenosis, and valvular fusion anomalies. Infectious entities, degenerative conditions, and malignant lesions are also depicted. We discuss surgical techniques used to repair both congenital and acquired pulmonary valvular diseases and describe postoperative appearances of the PV on imaging.